GONAD MATURATION OF ANGLE FISH (Pterophyllum scallare) INDUCED BY LASER PUNCTURE EXPOSURE AT DIFFERENT TIME DURATION - Fadillah Disa Yolanda; Sukendi '; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A research was conducted from January-February 2016 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Science, University of Riau Pekanbaru. The purpose of the research was to evaluate the duration of laser puncture exposure on gonad maturation of angle fish (Pterophyllum scallare). Completely randomized design was used to analyze the gonad maturation at the different duration of laser puncture exposure (0, 15, 20, and 25) seconds. The shooting was done twice a week for 4 weeks. The brood fish were reared in 54 L aquarium tank (60x30x35 cm) and fed on 38% protein pellet plus 57% protein tubifex worm.The results of research showed that there was an effect of laser puncture exposure duration, on gonad maturation of angle fish (Pterophyllum scallare). The best duration of laser puncture to stimulate gonad maturation was 20 second. At the duration the maturation was reached in 35 days with gonado somatic indeks 6,3 %, fecundity 908 eggs, and eggs diameter 1.5 mm. The temperature range from 26-27 oC, pH 5-6, and DO 5,7-6,8 ppm.Key words : laser puncture, gonad maturation, angle fish